The ability of Pisum sativum plant to use tricalcium super phosphate (TSP) in the presence and absence of mycorrhizal fungi under field conditions - Baghdad Science Journal (مجلة بغداد للعلوم)
Efficiency of Pisum sativum plants in using tricalcium super phosphate (TSP) in presence and absence of mycorrhizal fungi was evaluated in the field experiment in College of Science / Al-Mustansiriyah University. The experiment comprised of (6) treatments prepared from the interaction of two levels of inoculation [non-inoculation with fungus F0 and inoculation with Glomus mosseae fungus (F1)]. And three levels of phosphorus: 0,20,40 Kg P/ha. The experimental size was (1x2)m. Irrigation and hand-weeding were done when needed. The following plant measurements were recorded: (Shoots dry weight, concentration of N and P% in addition to percentage of root infection with mycorrhizal fungi at flowering 50% of plants. The results of the experiment could be summarized as following: Inoculation with Glomus mossease caused in a significant increase in all experimental measurements as compared with non-inoculation treatments under all levels of phosphorus that have used in the experiment. Highest values for the experiment measurements were recorded in the treatment that inoculated with (F1) and fertilized with 20 Kg P/ha. They were (3.65, 0.49, 3.10 and 85) for shoot dry weight gm/plant, P concentration, N concentration % and percentage of root infection respectively. As compared with (1.81, 0.24, 2.18 and 30) as significant least values for above measurements respectively in treatment non-inoculated and unfertilized. Application of phosphorous in level 40Kg P/ha significantly increasing the shoot dry weight, P concentration in non-inolcultion treatments as compared with the same treatments that fertilized with 20 Kg P/ha or un-fertilized.